Two new acremonium-like species, Paragibellulopsis sinensis sp. nov. and Phialoparvum sinense sp. nov. (Sordariomycetes, Ascomycota) from China - Heng Pan; Shuo-Qiu Tong; Zeng Chen; Yun-Jie Wu; Yi Wang; Gang Tao; Zhi-Yuan Zhang (MycoKeys)
Paragibellulopsis and Phialoparvum, both erected in 2018, currently comprise merely one and three validly published species, respectively. The identification of two new species, Paragibellulopsis sinensis and Phialoparvum sinense, was achieved by analyzing morphological characteristics and phylogenetic data obtained from four molecular markers (ITS, LSU, rpb2, and tef-1α). Morphologically, Pa. sinensis possessed short conidiogenous cells and aseptate and smaller conidia. On the other hand, Ph. sinense had obovate conidia and longer phialides. Phylogenetic analysis revealed that Pa. sinensis formed an independent branch as a sister species to Pa. chrysanthemi, whereas Ph. sinense clustered in a monophyletic clade with a stable topology. The maximum likelihood bootstrap ratio and the Bayesian inference posterior probability provided robust statistical evidence, indicating the presence of two novel species within the genera of Paragibellulopsis and Phialoparvum. The present study contributes to the discovery of species diversity in Paragibellulopsis and Phialoparvum.